Osteoarthritis in Football: With a Special Focus on Knee Joint Degeneration. (April 2017) - Salzmann, Gian M.; Preiss, Stefan; Zenobi-Wong, Marcy; Harder, Laurent P.; Maier, Dirk; Dvorák, Jirí
Football is currently the most popular sporting activity in the world. Multiple reports have shown that a high incidence of osteoarthritis is found in football players. Evidence clearly shows that traumatic injury significantly predisposes players for such pathophysiology. Injuries are frequent in amateur as well as professional football players, with knee and ankle accounting for the most severe injuries. Many professional athletes lose playing time due to injuries and many are forced into early retirement. Posttraumatic osteoarthritis is a common finding among ex-football players with numbers well above the normal population. Today's surgical techniques are advanced and capable of restoring the joint to a certain extent. However, a restitution ad integrum is reached only in very rare cases. Professional football players that return to play after serious injuries perform their extremely strenuous activity on morphologically compromised joints. Incomplete rehabilitation and pressure to return to play after an injurious event clearly put the athlete at an even higher risk for joint degeneration. Prevention strategies, improved surgical management, strict rehabilitation, as well as future aspects such as early suppression of inflammation, personalized medicine, and predictive genomics DNA profiling are needed to reduce incidence and improve the health perspectives of football players.